2015
DOI: 10.13037/rbcs.vol13n43.2473
|View full text |Cite
|
Sign up to set email alerts
|

Fatores determinantes da adesão de hipertensos a conduta dietoterápica

Abstract: resumo Introdução: No Brasil, a hipertensão é um grave problema para a saúde pública. Cerca de 17 milhões de brasileiros são hipertensos, dos quais 35% são adultos com 40 anos ou mais. Objetivo: O estudo objetivou avaliar os fatores determinantes da adesão de hipertensos a uma conduta dietoterápica. Metodologia: Trata-se de um estudo exploratório descritivo, de abordagem qualitativa, realizado em um município do noroeste do Rio Grande do Sul, com 95 adultos e idosos cadastrados como hipertensos no programa Est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…In addition, other studies point to issues related to the nature of chronic diseases such as the absence of symptoms in the early stages, the lack of severity and chronicity and an unsatisfactory doctor-patient relationship and inadequate multidisciplinary approach (23,25,27,31). Still, Massing and Portela (2015), in a descriptive exploratory study in 3978 hypertensive patients found that the evaluated did not associate the pressure control diet, but only the use of the drug (32).…”
Section: (1607%) Reason 4 -Individual and Behavioral Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, other studies point to issues related to the nature of chronic diseases such as the absence of symptoms in the early stages, the lack of severity and chronicity and an unsatisfactory doctor-patient relationship and inadequate multidisciplinary approach (23,25,27,31). Still, Massing and Portela (2015), in a descriptive exploratory study in 3978 hypertensive patients found that the evaluated did not associate the pressure control diet, but only the use of the drug (32).…”
Section: (1607%) Reason 4 -Individual and Behavioral Characteristicsmentioning
confidence: 96%
“…Massing and Portela, in a descriptive exploratory study conducted with hypertension showed that cultural factors also exerted a strong influence on adherence to dietary treatment, which requires major change in eating habits, lifestyle and even the personal beliefs (32). It is known that the power related aspects are difficult to be modified, because changing old patterns comprises components of individual history, family and social group (7,22).…”
Section: (1607%) Reason 4 -Individual and Behavioral Characteristicsmentioning
confidence: 99%
“…Há, ainda, a possibilidade de intervenção com medidas educacionais que objetivem explorar a prevenção e enfatizar os tratamentos não medicamentosos, por meio das mudanças nos hábitos de vida. Diversos estudos já confirmaram que problemas como obesidade, sedentarismo e estresse aumentam o surgimento de HAS e todas as consequências que esta acarreta (MASSING;PORTELLA, 2015;MACHADO et al, 2016;PELAZZA et al, 2020).…”
Section: Revisão Bibliográficaunclassified
“…Segundo Oliveira et al (2017) ações focadas em modificações do estilo de vida são mais promissoras no ambiente da APS. Dessa forma, toda a equipe de saúde deve trabalhar na elaboração de um plano educacional que vise a orientação da população com relação a prática de atividades físicas regulares, redução do consumo de álcool e do tabagismo, além de medidas dietoterápicas como redução do consumo de sódio, lipídios, alimentos não protetores, açúcares, entre outros (GIACHINI et al, 2019, COSTA et al, 2021MASSING;PORTELLA, 2015).…”
Section: Revisão Bibliográficaunclassified
“…As abordagens terapêuticas para o tratamento podem ser de duas formas: o tratamento não farmacológico que traz a proposta de modificações do estilo de vida, e o tratamento farmacológico ou medicamentoso [8]. Algumas recomendações gerais, como a dieta hipossódica, a manutenção do peso corporal, assim como uma alimentação saudável, a realização de exercícios físicos, e o abandono do hábito de fumar são cuidados importantes [9].…”
Section: Introductionunclassified